2021
DOI: 10.3390/ijms22147468
|View full text |Cite
|
Sign up to set email alerts
|

Effects of (R)- and (S)-α-Hydroxylation of Acyl Chains in Sphingosine, Dihydrosphingosine, and Phytosphingosine Ceramides on Phase Behavior and Permeability of Skin Lipid Models

Abstract: Ceramides (Cers) with α-hydroxylated acyl chains comprise about a third of all extractable skin Cers and are required for permeability barrier homeostasis. We have probed here the effects of Cer hydroxylation on their behavior in lipid models comprising the major SC lipids, Cer/free fatty acids (C 16-C 24)/cholesterol, and a minor component, cholesteryl sulfate. Namely, Cers with (R)-α-hydroxy lignoceroyl chains attached to sphingosine (Cer AS), dihydrosphingosine (Cer AdS), and phytosphingosine (Cer AP) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Comparison of Bilayer and Multilayer Structures. As noted earlier, experimental SC lipid membrane systems exhibit multilayer structures, which, for a typical lipid deposition of between 0.9 and 1.5 mg/cm 2 , 18,76,77 produce lipid membranes that are more than 10 μm thick. This corresponds to a stack of more than a thousand, ∼6 nm SPP-type bilayers.…”
Section: ■ Materials and Methodssupporting
confidence: 54%
“…Comparison of Bilayer and Multilayer Structures. As noted earlier, experimental SC lipid membrane systems exhibit multilayer structures, which, for a typical lipid deposition of between 0.9 and 1.5 mg/cm 2 , 18,76,77 produce lipid membranes that are more than 10 μm thick. This corresponds to a stack of more than a thousand, ∼6 nm SPP-type bilayers.…”
Section: ■ Materials and Methodssupporting
confidence: 54%
“…The results are also consistent with a study of lipid model membranes, which reported that alphahydroxylation of CERs (CER[AS] and CER[AP]) decreased resistance to water loss. 38) On the other hand, the finding that the distribution of S-chain lengths in CER[ADS] and CER[AP] differed between the high-and low-TEWL groups (Table 2) suggests that the difference in the distribution of S-chain lengths affects the proportion of domains formed by packing structures. Figure 7 shows that in the chain length distribution of CER[ADS], there was generally a low proportion of long C22 saturated hydrocarbon chains in the high-TEWL group.…”
Section: Discussionmentioning
confidence: 99%
“…2S, 3R-sphingosine and 2S, 3S, 4R-phytosphingosine) together with Rα-hydroxy fatty acids have recently been studied. 5,6 For at least one marketed ceramide, AP, the α-hydroxy fatty acid component consists of the two diastereomers of which the natural R-isomer promotes tighter lipid packing and the authors conclude that it should be preferred compared with the unnatural S-isomer or the racemic version. 6 The representative structures of other types of molecules (pseudoceramides) that are used in skin-care products are shown in Figure 1b.…”
Section: Comment On "Clinical Significance Of the Water Retention And...mentioning
confidence: 99%